Analysis of Factors Responsible for the State of Women Participation in Governance in Edo State of Nigeria - Ainabor, Augustine Eguavuon; Ibe-Enwo, Grace Iyi (Journal of Gender and Power, 2024)
The paper analyzed the factors responsible for the state of women participation in Governance using Edo State of Nigeria as a case study. It examined the level of influence of women participation in state governance in Edo State of Nigeria. It also assessed as well the extent education influences women participation in the governance of Edo State of Nigeria. In order to achieve the above objectives, two hypotheses were formulated to guide the study. Questionnaire was used as the primary instrument for data collection. The population of the study was 4,625 key politicians across the three senatorial districts in Edo State while the sample size which was determined using the Taro Yamani formula was 368. The Chi-Square(X2) test of proportion was adopted in the analysis of data. After statistically analyzing the data obtained from the primary source, it was found that there is low participation of Edo Women in the governance of Edo State of Nigeria. It was also found that there is a relationship between educational attainment of women and their low participation in the state governance of Edo State of Nigeria. The implication of the study is that there is need for policy action on the part of the state government in order to encourage more women to participate in the governance of the state. The paper recommended among others that the Edo State government should as a matter of deliberate policy, encourage girl-child and women education to enable more women access quality education that will equip them to face men in the field of politics and governance in the state.